Advertising and Media Capture in Turkey: How Does the State Emerge as the Largest Advertiser with the Rise of Competitive Authoritarianism?. (October 2021) - Yanatma, Servet
This article examines the distribution of advertising in newspapers in Turkey and the impact of the government on the allocation, in particular, of official announcements and of advertising by partially state-owned enterprises and private companies loyal to the ruling party, as well as pressure on other commercial advertisers, during the rule of the Justice and Development Party between 2002 and 2020. It demonstrates that the government has, in the last decade, largely used the advertising sector as a "carrot and stick" tactic to control newspapers through the distribution of official announcements and advertising by state-owned enterprises. It further finds that the state has emerged in recent years as the largest advertiser financing the "captured media, " control of media ownership has proved to be not enough to ensure docile news media. Turkey has shifted to competitive authoritarianism in recent years, and this article demonstrates the selective allocation of advertising, which is a strong component of suppressing the independent media. The article uncovers the impact of government on advertising, using two data sets to show: (i) the total spend on official announcements received by each newspaper and (ii) how much advertising space in square centimeters state-owned enterprises have placed in each newspaper. Interviews with editors-in-chief of newspapers also expose the direct role of government in the distribution of advertising.